2020
DOI: 10.1007/s13320-020-0587-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Leptospirosis Bacteria in Rodent Urine by Surface Plasmon Resonance Sensor Using Graphene

Abstract: In this paper, a graphene-coated surface plasmon resonance sensor is designed for the examination of Rodent urine which is responsible for Leptospirosis bacteria. Rodent urine is considered as sensing medium. Graphene surface is activated by phosphate-buffered saline solution for better attachment of Leptospirosis bacteria on its surface. Oliguria and Polyuria are the Rodent urine with high and low concentrations of Leptospirosis bacteria, respectively. The transfer matrix method is used for the formulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…A recent study reported the detection of Leptospirosis bacteria using a graphenebased SPR sensor [76]. The researchers coated a glass platform with graphene to effectively adsorb the bacteria.…”
Section: Graphene Oxide-based Spr Sensormentioning
confidence: 99%
“…A recent study reported the detection of Leptospirosis bacteria using a graphenebased SPR sensor [76]. The researchers coated a glass platform with graphene to effectively adsorb the bacteria.…”
Section: Graphene Oxide-based Spr Sensormentioning
confidence: 99%
“…For example, Thierry et al combined microbial incubation on chips with SPR detection to achieve rapid specific detection of Salmonella enterica serovar Enteritidis, Streptococcus pneumoniae and E. coli O157:H7 cultured on protein microarrays [ 65 ]. Several methods have also been proposed to further improve the sensitivity: A highly sensitive sensor based on surface material modification was constructed by modifying nanomaterials [ 67 , 68 , 69 ] (graphene, molybdenum disulfide, barium titanate) or organic compounds [ 59 ] (carbohydrate) on the surface of a gold chip, which can significantly improve the sensitivity of bacterial detection. Livache et al detected their interactions with bacteria by efficiently grafting simple carbohydrates onto the surface of a gold sheet and then using surface plasma resonance imaging during the process of culturing the bacteria on the surface.…”
Section: Surface Plasmon Resonance For Bacteria Detectionmentioning
confidence: 99%
“…interactions on a surface, including their kinetics, affinity and concentration (Skottrup et al 2008). In recent years, SPR biosensors have been used to detect avian influenza A viruses: H5N1 (Bai et al 2012) and H7N9 (Chang et al 2018), SIV: H1N1 (Yoo et al 2020), CSF (Mustafa et al 2014), PCV-2 (Hu et al 2014), Leptospira species (Raikwar et al 2020) and Brucella abortus (Gupta et al 2011).…”
Section: Biosensorsmentioning
confidence: 99%